Konsep Keadilan John Rawls terhadap Peran Wanita dalam Dunia Politik di Indonesia - Lingga, Leo Sugianto; Jebaru, Mathias Adon (Jurnal Analisis Sosial Politik, 2023)
Abstract The condition of women in politics is a major highlight in today’s world. The lack of women’s role in politics makes a decision in a country often a problem. The lack of women’s role in politics is influenced by a socio-cultural condition. In the Indonesian political world, which still adheres to a patriarchal culture, it is one of the factors that greatly affects the level of women’s roles in political culture. Patriarchal culture views the role of women from a gender perspective. Women are seen as weak to lead. The attitude or lack of role of women in politics is seen as one of the phenomena of injustice by John Rawls. John Rawls sees this injustice phenomenon as a form of lack of equality in the political world. John Rawls assumes and offers that women are one of the ways to decide justice in the state. In this paper the author uses the literature review method with the aim of describing the phenomenon of injustice faced by women. The author also found that there are factors that contribute to the lack of women’s role in politics.